Matlab-Simulink Modelling of 6/4 SRM with Static Data Produced Using Finite Element Method - (:unkn) unknown (BUDAPEST TECH, 2011)
The static performance of a switched reluctance motor (SRM) is investigated especially by using the finite element method (FEM) in the design and prototype development steps of the SRM in recent years. In order to determine the real working conditions of the motor, the dynamic behaviour of the SRM should be researched. For this purpose, this study has formed a dynamic model of a 6/4 SRM by using the motor's characteristics, such as inductance, flux and torque obtained by FEM, in Matlab-SIMULINK software. In addition, all the characteristics of the motor are obtained and discussed by using this dynamic model.
Keywords: Switched Reluctance Motor (SRM); Torque; Current Controller; Linear Model; SWITCHED RELUCTANCE MOTOR; SIMULATION